Earnings of Persons with Disabilities: Who Earns More (Less) from Entrepreneurial Pursuit? - Yang,Yang; Kulkarni,Mukta; Baldridge,David; Konrad,Alison (Equality, Diversity and Inclusion, 2022)
Earnings of Persons with Disabilities: Who Earns More (Less) from Entrepreneurial Pursuit? Abstract. Persons with disabilities (PWD) are among the largest and most diverse minority groups and among the most disadvantaged in terms of employment. Entrepreneurial pursuit is often advocated as a path toward employment, inclusion, and equality, yet few studies have investigated earning variation among PWD. Methodology. We draw on social cognitive career theory (SCCT) and disability employment and entrepreneurship literatures to develop hypotheses about who among PWD are likely to earn more (less) from entrepreneurial pursuits. We then conduct analyses on the nationally representative sample of Canadian Survey on Disability including all PWD engaged in entrepreneurial pursuit and match each to an organizationally employed counterpart of the same gender and race, and of similar age and disability severity (n ≈ 810). Findings. Entrepreneurial pursuit has a stronger negative association with earnings of PWD who experience earlier disability onset ages, who report more unmet accommodation needs, and who are female. Originality. First, this study applies SCCT to help bridge literatures on organizational employment barriers for PWD and entrepreneurs with disabilities. Second, we call into question the logic of neoliberalism about entrepreneurship by showing that barriers to organizational employment impact entrepreneurial pursuit decisions and thereby earnings. Third, we extend understanding of entrepreneurial earnings among PWD by examining understudied disability and demographic attributes. Lastly, this study is among the first to use a matched sample to empirically test the impact of entrepreneurial pursuit on the earnings of PWD. Keywords. disabilities, social cognitive career theory (SCCT), entrepreneurial pursuit, onset age, accommodation, disability origin
Keywords: Management

People with disabilities: Identity, stigmatization, accommodation, and intersection with gender and aging effects on employment opportunities. In Bendl, R., Bleijenbergh, I., Henttonen, E., & Mills, A. J., The Oxford Handbook of Diversity in Organisation - Baldridge,David; Beatty,Joy; Konrad,Alison; Moore,Mark (2018)
Disability status continues to have a significant negative impact on employment outcomes, even in countries with nondiscrimination policies, and outcomes differ by gender and age. These subpar outcomes can be linked to both environmental and psychological factors. The design of jobs and workplaces often limits the ability of workers with disabilities to contribute to their fullest capacity. Stigmatization on the basis of disability status reduces employer willingness to hire workers with disabilities and make reasonable accommodations to allow them to perform effectively. Some research indicates that women, older workers and workers with disabilities tend to be labeled as unwilling or unable to perform in demanding paid work roles. Age intersects with disability resulting in inappropriate attribution of disability status as “normal aging.” Gender intersects with disability to result in lower labor force participation for women with disabilities compared to their male counterparts. Exclusion and stigmatization create barriers to the development of a positive self-identity as a person with a disability, but such identity development can be empowering, creating a sense of pride and providing a basis for advocacy. Considerably more research is needed to understand how the actions of organizations, leaders, and teams affect the employment outcomes of workers with disabilities and how impacts differ by gender and age. But based upon extant knowledge, there are many actions employers can take to improve outcomes for this group of workers.
Keywords: Management

Childhood-onset disability, strong ties and employment quality - Baldridge,David; Konrad,Alison; Moore,Mark; Yang,Yang (Equality, Diversity and Inclusion, 2017)
Purpose Persons with childhood-onset disabilities are among the most marginalized populations, often unemployed or underemployment in jobs providing neither adequate hours for financial self-sufficiency nor fulfillment through skill-utilization. The purpose of this paper is to examine the extent to which social capital in the form of strong ties with family and friends is associated with enhanced employment outcomes for persons with childhood-onset disabilities. Design/methodology/approach Questioning the current theoretical consensus that strong social ties are unimportant to employment quality, the authors draw on disability research and opportunity, motivation and ability social capital theory to propose a model of the impact of strong ties with family and friends on paid-work-hours and skill-utilization as well as the potential moderating role of gender and disability severity. The authors then test this model using data from 1,380 people with childhood-onset disabilities and OLS regression analysis. Findings As theorized, family-of-origin-size is positively associated with hours worked. Family-of-origin-size is also associated with having more close friends and children. These strong ties, in turn, are positively associated with hours worked. The impact of having more children on hours worked and skill-utilization, however, is positive for men but non-significant for women. Originality/value This study breaks new ground by focusing on the association between strong ties with family and friends and employment quality for people with childhood-onset disabilities – a marginalized and understudied group. Findings further indicate the particular vulnerability of women with disabilities.
Keywords: Management

Workplace Inclusion of People with Disabilities: Toward Greater Understanding of the Role of Disability Attributes, Social Support and Barriers - Baldridge,David; Moore,Mark; Konrad,Alison (Annual Meeting of the Academy of Management, 2012)
Keywords: Management